Pendidikan Karakter melalui Kitab Ta’limul Muta’allim Berbasis Pesantren di Madrasah Mu’allimin Tambakberas Jombang - Faza, Muhammad; Idawati, Khoirotul; Hanifudin, Hanifudin (Lembaga Yasin AlSys, 2025)
Character formation is influenced by various factors, particularly the family and community environments in which an individual is raised. Good character leads to positive behavior, while poor character tends to result in negative actions. The term character, derived from the Latin character, refers to traits, dispositions, or morals that distinguish one individual from another. In this context, akhlak (morals) is a component of character embedded within an individual, which drives spontaneous good or bad actions without rational deliberation. This study aims to examine the formation of students’ character through the learning of the classical Islamic text Ta’limul Muta’allim at Madrasah Mu’allimin Mu’allimat. The research employs a qualitative case study approach, using observation and interviews with students and school administrators. The findings indicate that the classical learning methods applied at the madrasah contribute significantly to the moral development of students. Following the study of Ta’limul Muta’allim, students exhibited positive behavioral changes, especially in their respect toward kyai (religious leaders), teachers, dormitory administrators, and peers. However, some students still displayed undesirable behaviors in daily life, indicating the continued need for consistent moral guidance. The study concludes that moral education through classical texts plays a crucial role in shaping the character of students in pesantren-based madrasahs. Its implication is that strengthening character education rooted in Islamic values should be an integral part of the pesantren education system.